Methodology, strategies, and factors for business innovation in large companies - Daniel López Fernández; Miquel Oliver (International Journal of Innovation Studies, 2025)
Despite its recognized importance, innovation strategy remains an underexplored field, often hindered by fragmented approaches and practical barriers. To address this critical gap, this study develops a structured methodology for aligning innovation strategies with business objectives, offering a pathway to bridge the persistent divide between intent and execution. Drawing on qualitative insights from interviews with innovation leaders and informed by classical and contemporary theories, this research identifies the absence of standardized frameworks as a key challenge impeding innovation's integration into organizational strategy.The findings highlight systemic issues, including the frequent conflation of strategic vision with operational planning, the marginalization of innovation within executive leadership structures, and a narrow framing of innovation as solely technology-focused and supplemental rather than a central driver of business competitiveness and value creation. To extend beyond firm-level insights, the study underscores the interplay between organizational strategies and macroeconomic policies, emphasizing the necessity of collaborative ecosystems that foster open innovation.This work contributes to both the academic literature and organizational practice by providing actionable recommendations to overcome structural and cultural barriers, promote a top-down culture of innovation, and ensure strategic alignment. By advancing a robust framework for business innovation strategies, it empowers organizations to harness innovation as a cornerstone of long-term success in increasingly volatile and competitive markets.